Role of hippocampal location and radiation dose in glioblastoma patients with hippocampal atrophy - Le Fèvre, Clara (Radiat Oncol, 2021)
BACKGROUND: The hippocampus is a critical organ for irradiation. Thus, we explored changes in hippocampal volume according to the dose delivered and the location relative to the glioblastoma. METHODS: All patients were treated for glioblastoma with surgery, concomitant radiotherapy and temozolomide, and adjuvant temozolomide. Hippocampi were retrospectively delineated on three MRIs, performed at baseline, at the time of relapse, and on the last MRI available at the end of follow-up. A total of 98, 96, and 82 hippocampi were measured in the 49 patients included in the study, respectively. The patients were stratified into three subgroups according to the dose delivered to 40% of the hippocampus. In the group 1 (n = 6), the hippocampal D(40%) was < 7.4 Gy, in the group 2 (n = 13), only the H(contra) D(40%) was < 7.4 Gy, and in the group 3 (n = 30), the D(40%) for both hippocampi was > 7.4 Gy. RESULTS: Regardless of the time of measurement, homolateral hippocampal volumes were significantly lower than those contralateral to the tumor. Regardless of the side, the volumes at the last MRI were significantly lower than those measured at baseline. There was a significant correlation among the decrease in hippocampal volume regardless of its side, and D(max) (p = 0.001), D(98%) (p = 0.028) and D(40%) (p = 0.0002). After adjustment for the time of MRI, these correlations remained significant. According to the D(40%) and volume at MRI(last), the hippocampi decreased by 4 mm(3)/Gy overall. CONCLUSIONS: There was a significant relationship between the radiotherapy dose and decrease in hippocampal volume. However, at the lowest doses, the hippocampi seem to exhibit an adaptive increase in their volume, which could indicate a plasticity effect. Consequently, shielding at least one hippocampus by delivering the lowest possible dose is recommended so that cognitive function can be preserved. Trial registration Retrospectively registered. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13014-021-01835-0.